2021
DOI: 10.1002/bies.202000307
|View full text |Cite
|
Sign up to set email alerts
|

Physiological mediators of prenatal environmental influences in autism spectrum disorder

Abstract: Recent research has pointed to the importance of the prenatal environment in the etiology of autism spectrum disorder (ASD) but the biological mechanisms which mitigate these environmental factors are not clear. Mitochondrial metabolism abnormalities, inflammation and oxidative stress as common physiological disturbances associated with ASD. Network analysis of the scientific literature identified several leading prenatal environmental factors associated with ASD, particularly air pollution, pesticides, the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…The prevalence of ASD has steadily increased for the last decades [ 111 , 112 ]. Prenatal and early postnatal exposure to negative environmental factors, such as pollutants, chemical agents, infections, immune activation, and epigenetics have been associated with ASD [ 113 , 114 , 115 ]. These environmental factors, e.g., exposure to pesticides [ 116 ], maternal cigarette smoking [ 117 ], infective agents [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ], and immune stimulation [ 58 ], exhibit a significant impact on HERV expression.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ASD has steadily increased for the last decades [ 111 , 112 ]. Prenatal and early postnatal exposure to negative environmental factors, such as pollutants, chemical agents, infections, immune activation, and epigenetics have been associated with ASD [ 113 , 114 , 115 ]. These environmental factors, e.g., exposure to pesticides [ 116 ], maternal cigarette smoking [ 117 ], infective agents [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ], and immune stimulation [ 58 ], exhibit a significant impact on HERV expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to genetic factors, studies conducted to date indicate that environmental pollutants may also be involved as risk factors in the etiology of autism. For example, previous studies have shown that environmental pollutants can cause oxidative damage to DNA, disrupt epigenetic mechanisms (i.e., DNA methylation), and induce systemic neuroinflammation (for example, through the up/downregulation of cytokines) (Biswas, 2016; Frye et al, 2021; Theoharides et al, 2013); all of these mechanisms are known to be involved in the etiology and pathogenesis of autism. Two Chinese mother–child cohorts have similarly demonstrated that exposure to PAHs is associated with disruption of LINE1 methylation during neurodevelopment, which might disturb or aggravate alterations to normal neuronal plasticity and diversity (Kalia et al, 2017; Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that there is high heritability within families has driven the search for a genetic cause for ASD, but the empirical evidence suggests that the etiology is much more complex than a simple Mendelian inherited disorder [ 13 ]. Evidence now points to the importance of environmental–genetic interactions playing a prominent role in the etiology of ASD [ 14 ], particularly the prenatal environment [ 15 ]. Third, it is becoming clear that many children with ASD are medically complex [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%